Emotional competence in teachers at different educational levels: a review of the literature - Duncan-Villarreal, Verónica (2022)
Teachers need to know and develop a series of tools such as socio-emotional skills that allow them to identify their own emotions and those of others, therefore, contributing to the improvement of interpersonal relationships. The objective of the literature review was to describe original scientific studies regarding emotional competence in teachers at different educational levels. The methodology that was used was the guide of the PRISMA 2009 declaration, the scientific articles were selected from indexed journals of the Scopus, Scielo, Dialnet databases. The results were awarded based on the years between 2012 and 2021, 394 articles related to the topic were selected, but only 25 remained according to the established guidelines. It was concluded that there was a greater increase in scientific research on the subject in the years 2019 and 2020. The countries with the best influx of related articles are Spain and Brazil, as well as the classification of the articles of the different educational levels explains the importance in developing socio-emotional competencies. from the academic training of the teacher and its influence on professional practice.